Reta real: conceito imagem e conceito definição - Dias, Marisa da Silva (2006)
The study investigated concept image and concept definition related to the properties of the number line, and particularly the notion of density. The subjects were 45 teachers of secondary school mathematics (students aged 11-16 years) from São Paulo (Brazil). It was hypothesised that the teachers conceptions would match those of students in the age range that they teach. In order to validate this hypothesis, a diagnostic test was developed and the results of the teachers were compared with results obtained in both national and international studies of students conceptions. Analysis confirmed the hypothesis and indicated that both the concept image and concept definition used by the teachers were not coherent with formal. A sub-set of four teachers also participated in interviews developed with the aim of creating situations in which potential conflict factors would become cognitive conflict factors. Teachers reactions during these interviews indicated that these situations helped them to enhance to a higher intellectual stages in their reasoning about the number line